Acculturation and Cardiovascular Behaviors Among Latinos in California by Country/Region of Origin - Wieren, Andrew J. Van (2011)
Despite generally lower socioeconomic status and worse access to healthcare, Latinos have better overall health outcomes and longer life expectancy than non-Latino Whites. This “Latino Health Paradox” has been partially attributed to healthier cardiovascular (CV) behaviors among Latinos. However, as Latinos become more acculturated, differences in some CV behaviors disappear. This study aimed to explore how associations between acculturation and CV behaviors among Latinos vary by country of origin. Combined weighted data from the 2005 and 2007 California Health Interview Survey (CHIS) were used to investigate associations between acculturation level and CV behaviors among Latinos by country of origin. Among all Latinos, increased acculturation was associated with more smoking, increased leisure-time physical activity, and greater consumption of fast foods, but no change in fruit/vegetable and less soda intake. These trends varied, however, by Latino sub-groups from different countries of origin. Country of origin appears to impact associations between acculturation and CV behaviors among Latinos in complex ways.